Mengeksplorasi Pembudayaan Literasi Membaca Intra Kurikuler dan Ekstra Kurikuler di SDN 3 Glinggangan - Mustofa, Nurul Hadi; Markhamah, Markhamah; Sutama, Sutama (Lembaga Yasin AlSys, 2022)
This study aims to describe the implementation of the reading literacy movement through intracurricular and extracurricular activities at the habituation stage and to find out the supporting and inhibiting factors for the implementation of the school reading literacy movement through intracurricular and extracurricular activities at SDN 3 Glingangan. This type of research uses descriptive research with a qualitative approach, the subject of this research is Principals, Teachers, Students, data analysis techniques in this study using Miles and Huberman models. The data validity technique in this study used trigulation of techniques and sources. Based on the results of observations, interviews and documentation. From the results of research on the implementation of the reading literacy movement in schools through Intracurricular and Extracurricular Cultivation has been carried out, supporting factors in the form of awareness of school residents about the importance of reading literacy culture, student awareness, the existence of reading literacy facilities and infrastructure such as school library, reading corner, there are posters and wall magazines in the school environment, regular visits to the library, socialization of the reading literacy movement program and parental participation in reading literacy, Inhibiting factors include incomplete book collections, some reading corners have not used bookshelves .